Selective periarticular blocks for postoperative pain after hip and knee arthroplasty. Issue 4 (August 2021) - Balocco, Angela Lucia; Claes, Eveline; Lopez, Ana; Van Herreweghe, Imré
Abstract : Purpose of review: This review aims to provide an overview of selective periarticular blocks for postoperative pain after hip and knee arthroplasty and the current evidence for their use. Recent findings: Most interventional analgesia techniques for hip and knee arthroplasty result in a motor block and muscle weakness. Therefore, these are not well suited for fast-track protocols. In contrast, selective pericapsular infiltration techniques provide selective joint sensory block without an associated motor block. This facilitates postoperative pain management and avoids impairing ambulation and early rehabilitation. Summary: The pericapsular blocks of the hip (pericapsular nerve group block, iliopsoas plane block, hip block), genicular nerves block, and infiltration between the popliteal artery and the capsule of the knee play an increasingly important role in providing postoperative analgesia after hip and knee arthroplasty without impeding fast-track protocols. Abstract : Supplemental Digital Content is available in the text